2014
DOI: 10.5005/jp-journals-10019-1098
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Marginal Bone Level around Platform-Switched Implants

Abstract: Purpose: The long-term success of an implant depends on the stability of bone support for the implant. Most crestal bone loss occurs in the first year of implant placement. Platform-switching is an approach which can be clinically applied to preserve the crestal bone. The concept of 'platform switching' refers to the use of a smaller-diameter abutment on a larger-diameter implant collar. The purpose of the present study was to evaluate crestal bone level around platform-switched implants. Materials and methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The mean bone loss reported by studies also using platformswitched implants ranged from 0.30 to 0.95 mm; values consistent with the findings of the present study. In contrast, a significantly greater bone loss, reaching 2.1 mm, has been recorded for platform-matched implants (Vela-Nebot et al 2006;Cappiello et al 2008;Canullo et al 2009;Cocchetto et al 2010;Gultekin et al 2013;Calvo-Guirado et al 2014). Recent systematic reviews and meta-analyses have demonstrated the more favorable effect of the platform-switching design in reducing marginal bone resorption.…”
Section: The Concept Of Platform Switchingmentioning
confidence: 99%
“…The mean bone loss reported by studies also using platformswitched implants ranged from 0.30 to 0.95 mm; values consistent with the findings of the present study. In contrast, a significantly greater bone loss, reaching 2.1 mm, has been recorded for platform-matched implants (Vela-Nebot et al 2006;Cappiello et al 2008;Canullo et al 2009;Cocchetto et al 2010;Gultekin et al 2013;Calvo-Guirado et al 2014). Recent systematic reviews and meta-analyses have demonstrated the more favorable effect of the platform-switching design in reducing marginal bone resorption.…”
Section: The Concept Of Platform Switchingmentioning
confidence: 99%
“…In addition, Kapoor et al 13 observed that bone loss value in platform-switched implants was not significantly different between the mesial and distal sides of crestal bone. In another study, no significant differences were observed between the two types of platform-switched implants (Nobel Active and Nobel Replace Groovy).…”
Section: Discussionmentioning
confidence: 98%
“…Many of the previous studies have been undertaken 3‒12 month after surgery 13-15 , and the investigation of implants 24 months after implant placement is scarce. Therefore, the aim of the present study was to assess the amount of bone loss around the platform-switched and non-platform-switched implants 24 months after placement of implants.…”
Section: Introductionmentioning
confidence: 99%